Men's activism to end violence against women : voices from Spain, Sweden and the UK - Westmarland, Nicole (Policy Press, 2021)
EPUB and EPDF available Open Access under CC-BY-NC-ND licence. This book draws attention to those men who take action to end violence against women. The authors demonstrate what we can learn from their experiences to help build the movement to end violence against women.